UTILIZING PICTURE SERIES AS MEDIA TO ENHANCE STUDENTS' SPEAKING AT THE SECOND GRADE STUDENTS OF SMP NEGERI 1 TANIMBAR UTARA - Lambiombir, Sipra Agustina; Titirloloby, Piter; Luturmas, Jusuf (PT. LITERASI SAINS NUSANTARA, 2024)
Speaking is a crucial language skill encompassing the ability to pronounce words, convey ideas, thoughts, and opinions effectively. Despite its significance, many students exhibit a preference for their native language, such as Indonesian, over English. This study investigates the efficacy of utilizing picture series as a tool to improve students' English speaking proficiency at the second grade level of SMP Negeri 1 Tanimbar Utara. The research question addressed is whether picture series as a medium can enhance students' speaking ability. The objective is to explore how picture series as a medium can facilitate students' speaking skill development and improve their English language learning experience. This study adopts an experimental and quantitative research approach with a sample population of 50 students. The research instruments include a Speaking Skill Test and a Rating Scale of Speaking Skill Test. Data collection methods consist of Pre-Test and Post-Test assessments. The findings reveal a significant correlation between the use of picture series as a media and the enhancement of students' speaking skills. The validity test conducted through SPSS 25 confirms the suitability of the questionnaire items for research purposes. Overall, the results suggest that employing picture series as a teaching aid can effectively bolster students' speaking abilities, particularly for second-grade students at SMP Negeri 1 Tanimbar Utara.